An Educational Evaluation of Thiel Cadavers as a Model for Teaching Suturing Skills to Dental Students during the COVID-19 Pandemic - Michaelina Macluskey; Angela S. Anderson; Mark Gribben; Simon D. Shepherd (MDPI AG, 2022)
Suturing is an essential skill in dentistry and not one easily acquired. The COVID-19 pandemic prompted a change to the use of Thiel cadavers and online resources with the aim of improving skill acquisition using the best model available. This study investigated the utility of the Thiel cadaver for teaching suturing skills and the potential impact of the lockdown. Fifty-seven year 4 students attended a teaching session. Student views on this teaching were explored via a questionnaire survey and qualitative data collected from a focus group. Data were analysed using an inductive approach. The response rate was 53% (30 students) for the questionnaire with 9 students participating in the focus group. Independent feedback was provided by two members of the teaching staff. Online video resources were very well received by the students with 97% agreeing that it was useful preparation. Ninety percent (90%) thought that the cadaveric model was suitable for this teaching and realistic. Positive emergent themes from the focus group centred on the use of the cadaveric model and the positive and relaxed teaching and learning environment. Staff perceived this model as superior to previously used models. There were no reported negative pandemic impacts and the cadaver model was well received.